Population dynamics and the management of the Indo-Pacific king mackerel Scomberomorus guttatus from the upper Bay of Bengal off Bangladesh coast (Bangladesh Veterinarian, 2011)
Growth and mortality parameters, exploitation rates, annual recruitment patterns and length-weight relationships were estimated using FiSAT program from monthly length-frequency and weight samples of Indo-Pacific king mackerel, Scomberomorus guttatus, captured mainly by drift gill nets from the upper Bay of Bengal off Bangladesh coast. The aim was to estimate growth parameters, mortality rates, exploitation rate and recruitment pattern of S. guttatus for sustainable management. The von Bertalanffy growth parameters asymptotic length L∞ (cm) and growth constant K (per year) were 73.5 and 0.6, respectively. The L∞ and Z/K estimates provided by Wetherall plot were 73.3 and 2.3 cm. The annual rate of fishing mortality (F = 0.806) was low compared to the relatively high natural mortality (M = 0.994). The exploitation rate (E = 0.45) shows that the species was not over-exploited in the region. About 77.1% of S. guttatus were recruited during May-July and 23.0% during September-October. The growth performance index (φ′) was 3.5. The total length and body weight relationship was W = 0.0101 L 2.8622 suggesting that the growth rate was negative allometric (b